Clinical and metabolic correlates of women with polycystic ovary syndrome (PCOS) in a semi-urban community in Sri lanka. - Kumarapeli, V.; Seneviratne, R De A.; Dodampahala, R.; Wijeyaratne, C.N. (Community Medicine, Ministry off Health, Colombo, 2007)
INTRODUCTION Metabolic derangements associated with PCOS may predispose women to a range of diseases with attendant morbidity and mortality risks: type 2 diabetes mellitus, hypertension, dyslipidaemia and metabolic syndrome. OBJECTIVE To assess clinical and metabolic correlates of Sri Lankan women with PCOS. METHODS A case control study was carried among 146 newly diagnosed women with PCOS detected by a community based cross sectional survey that screened 3030 women aged 15-39 years in the district of Gampaha, in 2005; and 170 age matched controls selected from the same community. PCOS case definition was based on Rotterdam 2003 revised diagnostic criteria. RESULTS Delayed resumption of regular cycles following menarche occurred 9.1 times (95 percent CI 5.52-15.0) and pubertal onset excess weight gain occurred 2.48 times (95 percent CI 1.21-5.10) more frequently in the PCOS group. Prevalence of abdominal and generalized obesity was significantly higher (p<0.01) among cases than controls: abdominal obesity - waist hip ratio WHR>0.85 was 57.1 percent (PCOS) vs. 41.2 percent (controls); generalized obesity - BMI > 25 was 43.5 percent (PCOS) vs. 26.5 percent (controls). WHR >0.85 occurred 1.9 (95 percent CI 1.22-2.98) times and BMI > 25 occurred 2.14 (95 percent CI 1.34-3.43) times among cases than controls. Cases had significantly higher (p<0.001) mean fasting plasma insulin level 7.2 _u/ml; (PCOS) vs., 5.8 _u/ ml (controls). Prevalence of abnormal triglycerides (19.7 percent vs. 8.8 percent), abnormal LDL (17.7 percent vs. 7.1 percent), hypertension (10.9 percent vs 4.1 percent). and the metabolic syndrome (31.3 percent vs 17.1 percent) was also significantly higher (p<0.05) among cases than controls: CONCLUSIONS AND RECOMMENDATIONS PCOS has long term effects on the metabolic status of affected women especially metabolic syndrome. Greater care is essential from the time of their diagnosis.
Keywords: PCOS; SEMI URBAN; Sri Lanka